2014
DOI: 10.2478/intag-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil sieving on respiration induced by low-molecular-weight substrates

Abstract: A b s t r a c t. The mesh size of sieves has a significant impact upon soil disturbance, affecting pore structure, fungal hyphae, proportion of fungi to bacteria, and organic matter fractions. The effects are dependent upon soil type and plant coverage. Sieving through a 2 mm mesh increases mineralization of exogenously supplied carbohydrates and phenolics compared to a 5 mm mesh and the effect is significant (p<0.05), especially in organic horizons, due to increased microbial metabolism and alteration of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 18 publications
0
22
1
Order By: Relevance
“…While examining inferences based on such studies, it has to be kept in mind that there can be inherent bias in some of the procedures used. Sieving of soil can bring about change in microbial activity and community composition [94][95][96]. Bias associated with DNA extraction and PCR and sequencing techniques are also known [97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…While examining inferences based on such studies, it has to be kept in mind that there can be inherent bias in some of the procedures used. Sieving of soil can bring about change in microbial activity and community composition [94][95][96]. Bias associated with DNA extraction and PCR and sequencing techniques are also known [97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…The orientation, adsorption, and diffusion of the ligninolytic enzymes in the soil solid phase affect the lignin degradation in soil [31]. In laboratory studies, the impact of soil particle size on soil respiration was observed by Datta et al, which can, in turn, affect lignin degradability in soil [32].…”
Section: Lignin Degradation In Soilmentioning
confidence: 99%
“…Soil sieved through fine size mesh shows greater enzymatic activity than sieved through bigger mesh size sieve. This is due to exposure of a greater enzyme-adsorbed soil surface area to the substrate (Datta et al, 2014).…”
Section: Enzyme Organic Matter Interactionsmentioning
confidence: 99%
“…In the case of faster diffusion, the reaction will be enzyme limited. In most of the soil conditions, the enzymatic activity is usually low, compared to the large surface area of soil (Datta et al, 2014).…”
Section: Substrate Diffusionmentioning
confidence: 99%